Differences in characteristics and use of complementary and alternative methods for coping with endometriosis-associated acyclic pelvic pain across adolescence and adulthood - Mongiovi, Jennifer M.; Wallace, Britani; Goodwin, McKenzie; Vitonis, Allison F.; Karevicius, Sarah; Shafrir, Amy L.; Sasamoto, Naoko; DiVasta, Amy D.; Sieberg, Christine B.; Terry, Kathryn L.; Missmer, Stacey A. (Frontiers in Reproductive Health, 2024)
Introduction Over four million women in the US alone have been diagnosed with endometriosis. For those living with this disease, surgery and hormonal treatment reduce associated pelvic pain in some, while others continue to experience life impacting pain. Therefore, identification of accessible and cost-effective methods of pain reduction to compliment current treatment is urgently needed. Our objective was to quantify the prevalence of complementary and alternative methods used to manage acyclic pelvic pain and their reported benefit among women of different age groups living with endometriosis. Methods We used baseline questionnaire data from laparoscopically-confirmed endometriosis cases who completed a WERF EPHect compliant questionnaire in the longitudinal cohort of The Women's Health Study: From Adolescence to Adulthood (A2A). Participants with acyclic pelvic pain were asked to indicate specific methods or activities that either helped or worsened their pelvic/lower abdominal pain. Differences among age groups [adolescent (<18 years), young adult (18–25 years), and adult (>25 years)] were assessed using Fisher's exact test. Results Of the 357 participants included in analysis, sleep for coping was reported more frequently among adolescents (n = 59, 57.3%) compared to young adults (n = 40, 44.0%) and adults (n = 19, 31.1%; p = 0.004). Adolescents also reported more frequent use of music (n = 29, 21.2%) than young adults (n = 10, 7.0%) and adults (n = 7, 9.1%; p = 0.001). Exercise worsened pain most commonly among adolescents (n = 82, 59.9%), followed by younger adults (n = 67, 46.9%), and adults (n = 27, 35.1%; p = 0.002). Discussion Our analysis of participants in the A2A cohort showed that the prevalence of complementary and alternative methods used for coping with endometriosis-associated acyclic pelvic pain varied by age group. Future studies should aim to provide information that will further inform decisions in making care plans for managing endometriosis-associated pain that is effective, accessible, and tailored to the preferences of the patient.